Imitators and optimizers in Cournot oligopoly - Burkhard C. Schipper (University of California, Department of Economics, 2005)
We analyze a symmetric n-firm Cournot oligopoly with a heterogeneous population of optimizers and imitators. Imitators mimic the output decision of the most successful firms of the previous round a la Vega-Redondo (1997). Optimizers play a myopic best response to the opponents' previous output. Firms are allowed to make mistakes and deviate from their decision rules with a small probability. Applying stochastic stability analysis, we find that the long run distribution converges to a recurrent set of states in which imitators are better off than are optimizers. This finding appears to be robust even when optimizers are more sophisticated. It suggests that imitators drive optimizers out of the market contradicting a fundamental conjecture by Friedman (1953).
Keywords: C72; D21; D43; L13; 330